2013
DOI: 10.12948/issn14531305/17.4.2013.08
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach Model of Risk, Control and Auditing of Accounting Information Systems

Abstract: The use of IT in the financial and accounting processes is growing fast and this leads to an increase in the research and professional concerns about the risks, control and audit of Accounting Information Systems (AIS [4]. In this context, risk and AIS control approach is central to both financial and IT audit processes and IT governance processes within the organization. In this study, researching financial and IT audit process relations, and using the concepts of risk and control, we developed and applied an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…In this respect, we conclude that the impact is positive, on an upward trend for the entire period under observation ranging within the optimal level of capital adequacy. However, factors could also be of interest here such as the socio-economic factors, the rule of law [40], board composition indicators such as gender related indicators [41] or the strategy implemented regarding risk management [42].…”
Section: Impact Of Igc On Performance In the Italian Banking Sectormentioning
confidence: 99%
“…In this respect, we conclude that the impact is positive, on an upward trend for the entire period under observation ranging within the optimal level of capital adequacy. However, factors could also be of interest here such as the socio-economic factors, the rule of law [40], board composition indicators such as gender related indicators [41] or the strategy implemented regarding risk management [42].…”
Section: Impact Of Igc On Performance In the Italian Banking Sectormentioning
confidence: 99%
“…This study explores the effect of the tone at the top in weakening the effect of IT controls in preventing unethical behavior. While IT controls are capable of preventing misuse of funds, they are deficient by themselves to create an ethical environment (Brandas et al, 2013). Organizations need to set the right tone at the top to build a culture where ethical decision-making is second nature.…”
Section: Discussionmentioning
confidence: 99%
“…In another body of literature, Ceran, Gungor and Konya (2016) studied the importance of the accounting information system in preventing the crises that were or will be experienced by businesses, the study revealed that the financial information obtained from the accounting information system is very important for the decision-making process of the businesses, and the accounting information system is protected against the financial crises. Additionally, Brandas, Stirbu and Didraga (2013) aimed to develop and test an integrated approach model of risk, control and auditing of the AIS on three cycles of business processes: purchases, sales and cash in order to improve the efficiency of the IT governance. The study confirmed that there is a medium level of risk for each cycle, and the correlation between risk, control and audit in the management information systems, offers the perception of a stable IT environment for the entity.…”
Section: Independent Variablesmentioning
confidence: 99%